Adolescent mothers’ conceptualisation of social support in Ibadan Urban Slum - Oyetunde, Oloruntomiwa; Omobowale, Mofeyisara (Ethiopian Journal of Reproductive Health, 2025)
Adolescent motherhood represents a global challenge, with significant implications for the holistic health and well-being of adolescent mothers and their offspring. Access to social support plays a critical role in mitigating the challenges faced by adolescent mothers. Consequently, understanding the context of social support among adolescent mothers residing in urban slums of Ibadan is essential for designing effective and needs-sensitive interventions and policies. This study employed a qualitative approach and a phenomenological design to explore the lived experiences of adolescent mothers. Using a purposive sampling method, 20 in-depth interviews were conducted with adolescent mothers. The research was carried out in Ibadan municipality, encompassing all five urban local government areas, with a pilot study conducted in Oluyole LGA. Data collection involved audio recording and direct transcription of interviews into English. Themes were identified through a systematic analysis that incorporated fieldnotes, reflective insights, and coded transcripts. Content analysis was used to examine the emerging themes and contextualize social support from the perspectives of the participants. Adolescent mothers conceptualized social support as iranlowo/aduroti—a construct encompassing the provision of resources, assistance, and interventions designed to address their specific needs and challenges. Participants noted that social support within their communities often transcended kinship ties but was insufficient to meet all their needs. Findings underscore the necessity of interventions aimed at enhancing the quality and efficacy of social support within informal networks.